Designing a User-Centered Facial Health Application (Glowessence) with Usability Testing - Anak Agung Adi Wiryya Putra; Kadek Wahyu Santika Putra; Arefcy Theneven Saban (International Journal Software Engineering and Computer Science (IJSECS), 2025)
The study is carried out for developing the UI (User Interface) and UX(UX) of Glowessence App that enables users to determine their skin type and choose suitable facial care treatment for them. UI/UX Design process involves the User-Centered Design (UCD) principle which is primarily based on customer comfort and finding user requirements. In this study, the method adopted is Design Thinking (5 steps) which started from Empath, Define, Ideate, Prototype and Test. A System Usability Scale (SUS) is used during the testing phase to test the app with 29 participants and an average of 87 was scored — which falls into the "Excellent" category. Research results show the significance that UI/UX design based on direct user feedback could improve the success rate at solving skin care problems, making people more comfortable. The biggest novelty of this study is in a user-centered design solution enhancing application accessibility for a wider audience.